2020
DOI: 10.1111/dmcn.14709
|View full text |Cite
|
Sign up to set email alerts
|

Rectus femoris transfer in children with cerebral palsy: comparing a propensity score‐matched observational study to a randomized controlled trial

Abstract: RCT Randomized controlled trial RFT Rectus femoris transfer ROM Range of motion SEMLS Single-event multilevel surgery AIM To test whether an observational study employing propensity score matching could accurately estimate the causal treatment effects of rectus femoris transfer (RFT) as part of single-event multilevel surgery (SEMLS) in ambulatory children with cerebral palsy. METHOD We used a large clinical database to derive a propensity score for treatment assignment (SEMLSAERFT) and used this score to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…The replication crisis in science is real. There are vanishingly few examples of important clinical gait studies being replicated or refuted [ 43 ]. To encourage open and transparent scientific practice, we are providing a detailed Rmarkdown file and a sample dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The replication crisis in science is real. There are vanishingly few examples of important clinical gait studies being replicated or refuted [ 43 ]. To encourage open and transparent scientific practice, we are providing a detailed Rmarkdown file and a sample dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The replication crisis in science is real. There are vanishingly few examples of important clinical gait studies being replicated or refuted (42). To encourage open and transparent scientific practice, we are providing a detailed Rmarkdown file and a sample dataset.…”
Section: Future Directionsmentioning
confidence: 99%
“…Causal inference has gained popularity over the years and has been validated by reproducing the results of RCTs and deriving accurate effects from synthetic data. For example, in the context of CP treatment, we have recently shown that a standard causal inference technique can accurately and precisely estimate the effects of rectus femoris transfer compared to an RCT (12). We have used similar methods to estimate the effect of SEMLS (13).…”
Section: Causal Inferencementioning
confidence: 99%